Proposal of Artifact to Measure Degree of Boldness in Business Social Actors - Nelson Rogeri; Manuel Meireles; Cida Sanches; Samuel Ferreira Jr.; Marcio Luiz Marietto (BAR: Brazilian Administration Review, 2020)
This work proposes an artifact oriented by Design Science (DS) methods for measuring the degree of boldness in business social actors, especially entrepreneurs and businesspeople. To construct the artifact, the work of Eysenck and Wilson (1975) was used. The methodological approach used was Design Science, as the present object of study is considered an information artifact and, as such, has functions of data processing, reducing entropy (vision of syntax), forming meaning (vision of representation), and achieving viability (vision of adaptation). To ensure the validity of the study, a sample of users made up of 30 organizational psychologists was used, selected by convenience. The results demonstrated that using the artifact allows to measure entrepreneurs’ degree of boldness, affording them greater assertiveness in choosing and structuring their business. The study has a number of implications for managerial practice since by using the artifact it is possible to measure an entrepreneur’s degree of boldness and allow more assertive choices and structuring of their business, all the while reducing the rate of micro and small businesses that die early. In the academic field, the artifact will enable research on the degree of boldness of businesspeople with diverse other organizational variables.